Alterations in Antioxidative Potential of Ocimum Cultivars as a Method to Characterize UV-B Tolerance - Satish Kumar Verma2, Abhishek Mathur2, Md. Aslam Siddiqui3, D.K. Gupta4; Brij M Sharma, Santosh Kumar Singh1 (Recent Research in Science and Technology, 2011)
The comparative alterations of UV-B tolerance and recovery on lipid peroxidation and modulation in the contents of free radicals, enzymatic and non-enzymatic antioxidants in leaves of Ocimum sanctum, Ocimum basilicum and Ocimum gratissimum were studied. Lipid peroxidation measured in terms of MDA level increased with UV-B doses and the ratio was higher in Ocimum basilicum compared to Ocimum gratissimum. Recovered leaves showed lower MDA content and hydroxide radicals. Ascorbate, flavonoid and proline contents increased highly in stressed and recovered leaves of Ocimum gratissimum compared to Ocimum basilicum with an increase in UV-B doses. Higher free radical scavenging capacity and more efficient antioxidant potential of Ocimum gratissimum cultivars were proved in vivo, using the thiobarbituric acid assay in liver and muscle assay systems of ovarian models. The present findings suggested that UV-B doses have modulated the antioxidative machinery of Ocimum cultivars, though the results proved that significant cultivars differ in responses to UV-B. Differences in responses are closely related to differences in the activities of antioxidants and overall growth responses. A significant conclusion can be drawn from the findings that improved tolerance to UV-B stress may be accomplished by increased capacity of antioxidant system of plants.